Proteogenomic Analysis Identifies a Novel Human SHANK3 Isoform - Benthani, Fahad (Int J Mol Sci, 2015)
Mutations of the SHANK3 gene have been associated with autism spectrum disorder. Individuals harboring different SHANK3 mutations display considerable heterogeneity in their cognitive impairment, likely due to the high SHANK3 transcriptional diversity. In this study, we report a novel interaction between the Mutated in colorectal cancer (MCC) protein and a newly identified SHANK3 protein isoform in human colon cancer cells and mouse brain tissue. Hence, our proteogenomic analysis identifies a new human long isoform of the key synaptic protein SHANK3 that was not predicted by the human reference genome. Taken together, our findings describe a potential new role for MCC in neurons, a new human SHANK3 long isoform and, importantly, highlight the use of proteomic data towards the re-annotation of GC-rich genomic regions.